SPATIOTEMPORAL VARIATION OF MESOSCALE CONVECTIVE SYSTEM TYPE PERSISTENT ELONGATED CONVECTIVE SYSTEM (PECS) IN INDONESIA - Maulana Firdaus, Irfans
Research on Mesoscale Convective Systems (MCS) in Indonesia has been studied to see the characteristics and distribution of MCS. Persistent Elongated Convective System (PECS) is one of the MCS type that can cause extreme weather. However, the PECS event and its characteristics in Indonesia has not been studied further to see the spatial and temporal variations of PECS in the Indonesian. This study examines Persistent Elongated Convective System (PECS) in Maritime Continent from 2010-2014. MERG Dataset with brightness temperature is used to identify PECS and as an input Grab ‘Em Tag ‘Em Graph ‘Em (GTG) tracking algorithm to gain a better understanding about spatiotemporal variation in Indonesia related to diurnal variation of PECS. Precipitation data is used to see relationship between PECS event and heavy rainfall. Totally, PECS events in 2010-2014 is 5.574 events which the transitional period MAM has most PECS events and longest duration of life. The PECS spread in the early morning on land and sea, while on day and night time, it is concentrated on land for the area of Java, Papua, and Southern Kalimantan. Java and Papua have the largest concentrate PECS events. The life phase of the PECS has diurnal cycle for land and open-ocean, while coastal has semidiurnal cycle. There are differences in peak times for each phase of the PECS on land, coastal, and open-ocean. In Indonesia, PECS has the smallest average maximum area than in USA and China but has the longest duration and largest eccentricity.